Citizenship as foundation of rights : meaning for America / Richard Sobel. - Sobel, Richard, 1949- (Cambridge University Press, 2016)
Citizenship as Foundation of Rights explores the nature and meaning of American citizenship and the rights flowing from citizenship in the context of current debates around politics, including immigration. The book explains the sources of citizenship rights in the Constitution and focuses on three key citizenship rights - the right to vote, the right to employment, and the right to travel in the US. It explains why those rights are fundamental and how national identification systems and ID requirements to vote, work and travel undermine the fundamental citizen rights. Richard Sobel analyzes how protecting citizens' rights preserves them for future generations of citizens and aspiring citizens here. No other book offers such a clarification of fundamental citizen rights and explains how ID schemes contradict and undermine the constitutional rights of American citizenship.